Mobilidade humana e evangelização. Contribuições a partir do contexto brasileiro - Lussi, Carmem (Revista eclesiástica brasileira, 2010)
The article presents an analysis of the elements that make of contemporary human mobility a challenging – but privileged – occasion for the missionary effort that the Church makes once more towards today’s Christian communities. Having drawn a general panorama with the characteristics of the actual migratory currents in Brazil, the text reflects theologically about human mobility starting with the categories of interculturality and alterity, and placing migration next to the other differences that confront the Church in its evangelizing task. In the final part of the text the Author presents three enriching implications of the relation between people’s mobility and ecclesial missionary work: dynamism with daring and faith, interpersonal relation as a priority and care for the life of the “other”.